2020
DOI: 10.1002/jmv.25768
|View full text |Cite
|
Sign up to set email alerts
|

A guideline for homology modeling of the proteins from newly discovered betacoronavirus, 2019 novel coronavirus (2019‐nCoV)

Abstract: During an outbreak of respiratory diseases including atypical pneumonia in Wuhan, a previously unknown β-coronavirus was detected in patients. The newly discovered coronavirus is similar to some β-coronaviruses found in bats but different from previously known SARS-CoV and MERS-CoV. High sequence identities and similarities between 2019-nCoV and SARS-CoV were found. In this study, we searched the homologous templates of all nonstructural and structural proteins of 2019-nCoV.Among the nonstructural proteins, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 41 publications
2
88
0
2
Order By: Relevance
“…Protein molecular modeling and related bioinformatics tool could provide significant insights to predict the potential variations in the protein structures and complexes. 29 In the present study, a comparative modeling and molecular superimposition revealed important variations in the intermolecular interaction between ACE2 alleles and SARS-CoV-2 spike protein. It is interesting to note that for two ACE2 alleles, rs73635825 (S19P) and rs143936283 (E329G), low binding affinity and lack of some of the key residues in the complex formation with SARS-CoV-2 spike protein could be suggestive of intrinsic resistance to some scale against the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 52%
“…Protein molecular modeling and related bioinformatics tool could provide significant insights to predict the potential variations in the protein structures and complexes. 29 In the present study, a comparative modeling and molecular superimposition revealed important variations in the intermolecular interaction between ACE2 alleles and SARS-CoV-2 spike protein. It is interesting to note that for two ACE2 alleles, rs73635825 (S19P) and rs143936283 (E329G), low binding affinity and lack of some of the key residues in the complex formation with SARS-CoV-2 spike protein could be suggestive of intrinsic resistance to some scale against the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 52%
“…It has attracted a great attention since published. Note however that COVID-19 is a new disease, our awareness and knowledge is gradually increasing based on the ongoing research findings and clinical practice experience [3][4][5][6][7][8]; hence, the strategies of diagnosis and treatment are also continually updated. For instance the Diagnosis and Treatment Guidelines for COVID-19 issued by the National Health Committee of the People's Republic of China (http://www.nhc.gov.cn/), among 16 January 2020 to 3 March 2020, has issued a total of seven editions with some contexts being substantively changed.…”
Section: Dear Editormentioning
confidence: 99%
“…The 3C-like protease (3CL pro ) is a cysteine protease that hydrolyses the viral polyproteins pp1a and pp1ab to produce functional proteins during coronavirus replication. Because of its highly conserved sequence and essential functional properties, 3CL pro has been validated as a potential target for the development of drugs to treat SARS, MERS and COVID-19 [9][10][11][12] . At present, a variety of natural and synthetic inhibitors targeting different sites and regions of 3CL pro have been developed [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%